Expression of COPI components during development of Drosophila melanogaster. - Grieder, N.C.; Kloter, U.; Gehring, W.J. (Gene expression patterns : GEP, 2005)
In a PlArB enhancer detector collection, a line was found that showed upregulated expression within centrally to posteriorly located germarial cysts. It was inserted in the gammaCOP locus on chromosome 3R. GammaCOP is a component of the COPI coatomer involved in membrane traffic. Most of the other known components of the COPI coatomer also showed higher expression in the posterior half of the germarium. Not only meiotic germline cysts but also migrating follicle cells upregulate the COPI subunits. During embryonic and larval development, the COPI subunits are expressed ubiquitously as expected for genes required for cell viability. In addition, they are strongly expressed in the salivary glands and the proventriculus. Whether tissue-specific transcriptional upregulation of COPI subunits is required for the reorganization of membranous compartments that are needed for the developmental processes that confer cyst polarity and follicle maturation will have to be addressed in a genetic study.